Changes to administrative controls in banks after the financial crisis. Issue 2 (18th June 2018) - Christensen, Leif; Rikhardsson, Pall; Rohde, Carsten; Batt, Catherine Elisabet
Abstract : Purpose: This paper aims to explore and explain how administrative controls have been changed as a response to a significant crisis, using the transition of the three largest Icelandic banks from bankrupt to operational entities after the 2008 financial crisis. The Icelandic banks are compared with three Danish banks to separate crisis-driven responses from simple market-driven reactions. Design/methodology/approach: Empirical data were collected using semi-structured interviews. The participating Icelandic and Danish banks were considered as two units, which formed the basis for a comparative case study between the two countries. Findings: Driven by an understanding of what is expected by the market rather than the need to inform and guide the employees the Icelandic banks implemented a number of revolutionary and formally documented changes. These changes included significant bigger risk management functions and policies and procedures documenting "everything". However, in both countries, it seems that new values supported by the "tone at the top", areas with limited formal documentation, are the most important management tools. Research limitations/implications: The study relies on interviews with employees, and the actual changes of administrative controls have not been reviewed. The most important implication is that the situated logics in Iceland driven by external institutional pressure initiated a revolutionary implementation of values bypassing existing routines and formalised rules. Originality/value: Although the use of management controls has been studied intensively, detailed studies of the banking sector have been lacking. Furthermore, there is limited knowledge of how administrative controls changed in response to the financial crisis.